1999
DOI: 10.1109/90.811456
|View full text |Cite
|
Sign up to set email alerts
|

Performance of ATM networks under hybrid ARQ/FEC error control scheme

Abstract: In ATM networks, fixed-length cells are transmitted. A cell may be discarded during the transmission due to buffer overflow or detection of errors. Cell discarding seriously degrades transmission quality. This paper analyzes a hybrid automatic repeat request/forward error control (ARQ/FEC) cellloss recovery scheme that is applied to virtual circuits (VC's) of ATM networks. FEC is performed based on a simple singleparity code, while a Go-Back-N ARQ is employed on top of that. Both throughput efficiency and reli… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
5
0

Year Published

2000
2000
2007
2007

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(5 citation statements)
references
References 9 publications
0
5
0
Order By: Relevance
“…It is observed that the number of basic patterns as given in column 5 is extremely small compared to the total number of patterns as given in column 2. The number of UBPs h,is obtained from the formula (9). The number of patterns generated from all RBPs V is calculated using the equation (8).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…It is observed that the number of basic patterns as given in column 5 is extremely small compared to the total number of patterns as given in column 2. The number of UBPs h,is obtained from the formula (9). The number of patterns generated from all RBPs V is calculated using the equation (8).…”
Section: Resultsmentioning
confidence: 99%
“…SPC codes and SPC product codes have been proposed for cell loss recovery in ATM networks. Simple cell loss recovery schemes based on SPC codes are found in [6]- [9]. M.A.…”
Section: Introductionmentioning
confidence: 99%
“…Specific hybrid ARQ/FEC protocols have also been studied with respect to ATM networks 1,5,6,7,8 . This paper provides general models with which to analyze stream throughput with and without FEC.…”
Section: Introductionmentioning
confidence: 99%
“…Simmon et al [13] SPC codes and SPC product codes for cell loss recovery in ATM networks. Simple cell loss recovery schemes based on SPC codes are found in [8][9][10][11]. Kousa and Mugaibel [12] extend the encoding to two dimensions, thus forming a product code.…”
Section: Introductionmentioning
confidence: 99%